Thromboembolic complications after electrical cardioversion in patients with atrial flutter - Elhendy, Abdou; Gentile, Federico; Khandheria, Bijoy K; Gersh, Bernard J; Bailey, Kent R; Montgomery, Samantha C; Seward, James B; Tajik, A.Jamil (The American journal of medicine, 2001)
To determine the incidence of thromboembolic complications after cardioversion in patients with atrial flutter. We reviewed 615 electrical cardioversions performed electively in 493 patients with atrial flutter. Embolic complications were evaluated during the 30 days after cardioversion. Follow-up data were obtained by follow-up visits and by contacting the treating physician. Anticoagulants had been administered in 415 cardioversions (67%). Cardioversion was successful in 570 procedures (93%). Three embolic events (in 3 patients) occurred in the 30 days after 550 successful cardioversions with completed follow-up (0.6% of successful procedures; 95% confidence interval, 0.1% to 1.6%). Two of the 3 patients had not been anticoagulated, whereas the third patient had subtherapeutic oral anticoagulation. No embolic event occurred in procedures performed with adequate anticoagulation. The incidence of embolism in patients regardless of subtherapeutic anticoagulation was 1% (3 of 303 successful cardioversions). We observed a low (0.6%) incidence of postcardioversion thromboembolic complications in patients with atrial flutter. Embolic events did not occur in patients with adequate anticoagulation.